Studies on the Seasonal Variation in the Chemical Composition of Khejri (Prosopis spicigera Linn.) - Gupta, M. L.; Mathur, C. S. (Indian Forester, 1974)
Samples of leans from top, middle and lower strata of six randomly selected khejri (Prosopis spicigera Linn.) trees were analysed in order to study the optimum period of lopping for livestock feeding. The crude protein, ether extract, crude fiber, nitrogen free extract, calcium and phosphorus were 16.00, 3.90, 14.18, 52.95, 2.32 and 0.24 per cent respectively on dry matter basis during winter suggesting maximum contents of crude protein, ether extract and calcium. Thus winter, when the shortage of forages prevailed, was found most suitable season for lopping khejri tree.